2014
DOI: 10.2337/diaspect.27.2.100
|View full text |Cite
|
Sign up to set email alerts
|

Novel Agents for the Treatment of Type 2 Diabetes

Abstract: In Brief Impaired insulin secretion, increased hepatic glucose production, and decreased peripheral glucose utilization are the core defects responsible for the development and progression of type 2 diabetes. However, the pathophysiology of this disease also includes adipocyte insulin resistance (increased lipolysis), reduced incretin secretion/sensitivity, increased glucagon secretion, enhanced renal glucose reabsorption, and brain insulin resistance/neurotransmitter dysfunction. Although curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 124 publications
(61 reference statements)
1
55
0
1
Order By: Relevance
“…Type 2 diabetes may remain undetected for many years and exhibit insulin resistance and other pathophysiologic abnormalities contributing to hyperglycemia referred to as the "ominous octet" shown in Fig. 3.1 [ 8 ]. In both type 1 and 2 diabetes, chronic hyperglycemia results in similar long-term complications.…”
Section: Diabetes: Presentation Prevalence Diagnosis and Managementmentioning
confidence: 94%
“…Type 2 diabetes may remain undetected for many years and exhibit insulin resistance and other pathophysiologic abnormalities contributing to hyperglycemia referred to as the "ominous octet" shown in Fig. 3.1 [ 8 ]. In both type 1 and 2 diabetes, chronic hyperglycemia results in similar long-term complications.…”
Section: Diabetes: Presentation Prevalence Diagnosis and Managementmentioning
confidence: 94%
“…It has been reported that caffeine may stimulate insulin secretion trough β pancreatic cells, due to the rise of intracellular Ca ++ (Park et al, 2009). In the skeletal muscle, insulin bind to its receptor causing the phosphorylation of the tyrosine of the receptor, resulting in insulin receptor substrates (IRS-1 and 2), IRS1 and 2 mediate the effects of insulin over glucose metabolism, through the activation of phosphatidylinositol (PI)-3 kinase and PKA/AKt and by the increase of GLUT4 and glycogen synthase (GS) (Defronzo, 2010). However, once the insulin receptor is not operating with its hormone, an insulin resistance occurs and the metabolism of glucose does not occur .…”
Section: Caffeine and Thyroid Hormonesmentioning
confidence: 99%
“…Fasting hyperglycaemia in all forms of diabetes mellitus occurs primarily as a result of upsurge in hepatic glucose synthesis (HGS) [1,2]. Two specific enzymes, glucokinase (GK) and glucose-6 phosphatase (Glu-6-Pase) play crucial role in hepatic glucose production, utilization and homeostasis [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%